Covid-19 pandemic and the social determinants of health - Paremoer, Lauren; Nandi, Sulakshana; Serag, Hani; Baum, Fran (BMJ (Online), 2021)
Lauren Paremoer and colleagues call for action to create a fairer and more sustainable post-covid world